2020
DOI: 10.1016/j.resconrec.2020.105044
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the production of biodiesel from urban wastewater-derived lipids

Abstract: Production of biodiesel is one of the most important European targets within renewables for the future. To consider biodiesel a feasible alternative to fossil fuel, unconventional resources need to be exploited. This review aims to provide up-to-date knowledge on the existing reuse of lipids from urban wastewater to produce biodiesel. Lipids are readily removed by mixed microbial populations during wastewater treatments in sewage plants. Assessment results on potential annual European market supply indicate 3-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(5 citation statements)
references
References 143 publications
0
5
0
Order By: Relevance
“…Robles et al (2020) described the state of the art of nutrient recovery by examining the benefits and limitations of different recovery technologies; they conclude too that more research is needed to optimize these recovery technologies and broaden their applicability. Frkova et al (2020) evaluated the technical feasibility of removing lipids from urban wastewater for biodiesel production and demonstrated that a non-negligible amount is extractable for the production of biofuels. However, the study also found that lipid recovery methods are still limited and none of them are currently used on a large scale.…”
Section: Pilot Circular Studies From Literaturementioning
confidence: 99%
“…Robles et al (2020) described the state of the art of nutrient recovery by examining the benefits and limitations of different recovery technologies; they conclude too that more research is needed to optimize these recovery technologies and broaden their applicability. Frkova et al (2020) evaluated the technical feasibility of removing lipids from urban wastewater for biodiesel production and demonstrated that a non-negligible amount is extractable for the production of biofuels. However, the study also found that lipid recovery methods are still limited and none of them are currently used on a large scale.…”
Section: Pilot Circular Studies From Literaturementioning
confidence: 99%
“…Cost-benefit analyses (CBAs), sensitivity analysis (SA), and scenario modeling are applied in the identification of key cost drivers, assessment of risk values, as well as optimization of process parameters that ensure big returns. Moreover, the results of techno-economic analysis do not only offer valuable insights into the competitiveness of biodiesel production using solid acid catalysts compared to the other methods of production of biodiesel but also contribute towards educated choices and strategic planning for the creation of sustainable and economically profitable businesses meant to produce biodiesel [97].…”
Section: Economic Viability and Techno-economic Analysismentioning
confidence: 99%
“…The cultivation of aquatic weeds on wastewater, such as duckweed, with the subsequent processing in biorefinery schemes to obtain multiple outputs, including ethanol, methane, and volatile fatty acids, has also been studied [35,36]. Other researchers have focused on individual elements that could be included when conceptualizing a biorefinery, such as the recovery of lipids from wastewater for the production of biodiesel [37] or the cultivation of cellulase on domestic wastewater [38]. Wastewater-based biorefinery schemes have been referred to as "wastewater biorefinery" [39,40].…”
Section: Biorefinery Application For Wastewatermentioning
confidence: 99%